Can vacuum insulation panels be cost-effective when applied in building façades?. (15th March 2021) - Simões, Nuno; Gonçalves, Márcio; Serra, Catarina; Resalati, Shahaboddin
Abstract: A key factor for achieving nearly-zero energy buildings is to reduce their energy demand using highly efficient thermal insulation materials, such as vacuum insulation panels (VIPs). Currently, the high investment cost of VIPs is hindering the technology penetrating the building market. However, their high thermal performance coupled with reduced thicknesses can lead to economic benefits associated with space savings, significantly changing the economic standing of VIPs. This study presents a comprehensive life cycle cost (LCC) analysis of the application of VIPs in external thermal insulation composite systems (ETICS) in office building façades performed from the landlord perspective. The proposed LCC methodology, based on the EU cost-optimal regulation, allows for comparing the cost-effectiveness of VIPs with conventional insulation materials, taking full account of the additional rental income due to space savings. Energy calculations are performed based on transient heat transfer. The study takes into account varying parameters, such as location, cost of materials, insulation thickness, and rental prices, among others. The results demonstrate that VIPs can be economically viable, in particular in cities where office full-leasing rental prices are high. The range of VIP and rental prices that make their use in buildings cost-effective are identified. For example, it is shown that for rental costs higher than 350 €/(m 2 .y) VIP can be cost-effective for a current market price of 3000 €/m 3, when local climate demands for thermal transmittance bellow 0.19 W/(m 2 .K). This analysis is useful for VIP manufacturers, project owners and landlords that may be looking for competitive insulation products. Highlights: Global costs for a vacuum panel system are compared with conventional insulation. A methodology for life cycle cost analysis, including rental costs, is used. Energy balance is determined with transient calculations for a unit area of wall. The influence of changing several technical and economic parameters is discussed. VIPs can be found to be cost-effective for buildings in high rent locations.